The impact of hallyu (korean wave) on academic performance and learning burnout in accounting students - Hidayat, Vinny Stephanie; Dewi, Nunik Lestari; Candra, Anastasya Regina (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study aims to analyze whether there is an influence of Hallyu on students' Academic Performance, in addition to that the dominant influence of Hallyu on Academic Performance, whether it has a positive or negative effect. Regarding the effect of Hallyu on academic performance the findings of several earlier studies vary. This study uses respondents from the current era in an effort to boost the value and knowledge associated with the research findings. This study uses descriptive & exploratory methods and hypothesis testing using regression analysis. University Students in the accounting study program and master's program in accounting for the 2020–2023 batch at one of the private universities in Bandung make up the study's population. The respondents have completed tax-related courses, such as international tax, tax planning, and taxation. The number of students in the research sample was 137. Surveys were distributed in order to gather data. The results of the study showed that Hallyu has a positive effect on student academic performance. Hallyu is able to reduce academic burnout in learning, thereby increasing student enthusiasm in learning/undergoing lecture activities. The results of the interviews with the respondents and the T-Test's significance value, which is less than 0.05, demonstrate this.This research can be used as a reference for academics to consider including Hallyu elements (including K-Drama and K-Pop in course materials used in the teaching and learning process in the classroom, for example in case studies regarding tax accounting, international tax, dan tax planning) to increase student interest in attending lectures, so that it is expected to improve student academic performance. This study specifically analyzes whether Hallyu can overcome learning burnout in students, or whether it only takes up study time and reduces students' academic performance.